Research on mid-infrared quantum cascade lasers spectral beam combining - Fan, Xinmin; Zhang, Jianxin; Wang, Yan; Li, Sensen; Wang, Chunyan; Wu, Yuantai; Zhang, Lujun; Huang, Xiaodong; Li, Shun; Zhang, Yu (Frontiers in Physics, 2024)
Quantum cascade lasers (QCLs) in the mid-infrared (MIR) hold significant potential for widespread applications in both military and civilian contexts. However, the utility of present single-chip QCLs is hampered by issues such as low output power and subpar beam quality. This study addresses these limitations by employing spectral beam combining (SBC) based on a diffraction grating, with an aim to enhance both power and beam quality of MIR QCLs. Coaxial power synthesis of three single-chip QCLs (around 4.75 μm) is achieved experimentally, importantly, the beam quality did not decrease after combining, essentially maintaining the same quality as before combining. It is proposed that there are four main factors affecting the combining efficiency, namely operating optical power (or driving current) of the chips, individual differences in QCL chips, diffraction grating, and reflectivity of feedback mirror, and their effects on the combining efficiency are discussed separately. This study confirms that SBC is an effective way to obtain high-power and high-beam quality MIR QCL sources, and lays a research foundation for more beam spectral combining.